2019
DOI: 10.1111/jphp.13027
|View full text |Cite
|
Sign up to set email alerts
|

Anti-alcohol liver disease effect of Gentianae macrophyllae extract through MAPK/JNK/p38 pathway

Abstract: Objectives The hepatoprotective effect of Gentianae macrophyllae root extract (GME) on alcoholic liver disease (ALD) was evaluated through ethanol induced ALD animal model. Methods Mice were randomly divided into control normal group (10 mice), ethanol‐induced ALD model group (10 mice) and GME plus ethanol group (30 mice). Mice in model group were given intragastric administration with 50% (v/v) ethanol aqueous solution (200 μl for each) once daily for 19 days. Mice in control normal group received equal volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Moreover, another critical finding of this study is that miR-155 activated the MAPK signaling pathway via SOCS1 to promote AH progression. It was previously reported that, through the inhibition of the phosphorylation of JNK and p38, Gentianae macrophyllae root extract (a constituent of traditional Chinese medicine) helped to attenuate alcoholic liver disease by constraining inflammation responses (Cui et al, 2019). Others have shown that miR-155 is involved in the mediation of inflammatory response and the MAPK signaling pathway (Zhu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another critical finding of this study is that miR-155 activated the MAPK signaling pathway via SOCS1 to promote AH progression. It was previously reported that, through the inhibition of the phosphorylation of JNK and p38, Gentianae macrophyllae root extract (a constituent of traditional Chinese medicine) helped to attenuate alcoholic liver disease by constraining inflammation responses (Cui et al, 2019). Others have shown that miR-155 is involved in the mediation of inflammatory response and the MAPK signaling pathway (Zhu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol dehydrogenase in the cytoplasm of liver cells will metabolize ethanol into acetaldehyde, aldehyde dehydrogenase (ALDH) or other isoenzymes. The lack of acetaldehyde dehydrogenase leads to the accumulation of acetaldehyde, and excess acetaldehyde produces a large amount of reactive oxygen species (ROS), which in turn leads to oxidative stress, hepatic stellate cells (HSCs) and cause severe hepatotoxicity (Cui et al 2019). In addition, the hepatocytes were directly stimulated by the ethanol and acetaldehyde accumulated in the liver, which can cause degeneration and necrosis of liver cells, and aggravate hepatocyte apoptosis (Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the active ingredients in natural medicinal plants have performed well in liver protection. For example, maltol treats CCl 4 -induced acute liver injury by inhibiting apoptosis and inflammatory response (Liu et al 2018); the mechanism of garlic protective polysaccharide on liver protective activity is detected by inhibiting TNF-a, TGF-b1 and core proteoglycan (Wang et al 2018); Gentian leaf extract can exert anti-inflammatory activity by inhibiting the translocation of NF-jB transcription activity (Cui et al 2019); Green tea extract can reduce liver inflammation by regulating Toll-like receptor (TLR) 2/3 (Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KCs play an important role in inflammation and hepatic homeostasis. Activated KCs are important in the pathogenesis and the progression of ALD as they induce an inflammatory cascade and release interleukin-1β (IL-1β), IL-6, IL-18, and other pro-inflammatory cytokines to aggravate liver damage (8,9). Chronic alcohol consumption may have an additional impact on the endoplasmic reticulum and mitochondria (10).…”
mentioning
confidence: 99%